Strength Properties of Processed Fly Ash Concrete - Anandan, Sivakumar; Sounthararajan, Vallarasu Manoharan (Journal of Engineering and Technological Sciences, 2015)
The present paper reports on the mechanical treatment of fly ash for improving the delayed reactivity of fly ash with the hydration product of cement. Grinding of fly ash was carried out in a ball mill for different time durations and processing time was optimized for maximum fineness. Concrete mixes were prepared using various proportions of processed and unprocessed fly ash replacement in cement (25% and 50%). The influence of steel fiber addition on the mechanical properties of the concrete was studied for different curing periods. The test results on pozzolanic activity and lime reactivity indicate that the processed fly ash exhibited a higher strength gain than the unprocessed fly ash, with a maximum increase in compressive strength of up to 12%. Improved pozzolanic properties were noticed due to the increase in fineness of the fly ash particles.